2020
DOI: 10.1101/2020.03.11.986844
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atypical chemoreceptor arrays accommodate high membrane curvature

Abstract: The prokaryotic chemotaxis system is arguably the best-understood signaling pathway in biology, but most insights have been obtained from only a few model organisms. In all previously described species, chemoreceptors organize with the histidine kinase (CheA) and coupling protein (CheW) into a hexagonal (P6 symmetry) extended array that is considered universal among archaea and bacteria. Here, for the first time, we apply cryo-electron tomography to whole Treponema denticola (Td) cells to investigate the struc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…We show that while the bacterial pathogen V. cholerae is completely inactivated by UVC, the cell’s ultrastructure is indistinguishable from untreated samples. More specifically, using the F6 chemotaxis array as an example, we show that the STA results (reaching resolutions between 2-3 nm) are similar to the published literature for complexes of similar size and in cells with similar thicknesses (Berger et al, 2021; Wolff et al, 2020; Yang et al, 2019; Muok et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…We show that while the bacterial pathogen V. cholerae is completely inactivated by UVC, the cell’s ultrastructure is indistinguishable from untreated samples. More specifically, using the F6 chemotaxis array as an example, we show that the STA results (reaching resolutions between 2-3 nm) are similar to the published literature for complexes of similar size and in cells with similar thicknesses (Berger et al, 2021; Wolff et al, 2020; Yang et al, 2019; Muok et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…Previous findings show that this additional domain, called CheR like , is widespread among the spirochaetes (Fig. 1B) 29,30 . It is a distant homolog of the chemotaxis protein CheR, which methylates receptors using the methyl-donor S-adenosyl methionine (SAM) as part of an adaptation response 31,32 .…”
Section: Introductionmentioning
confidence: 60%
“…Furthermore, it has been recently shown that Td cells can actively move from oral cavities to brain tissues where they induce structures associated with Alzheimer’s disease in mice 28 , although the role of chemotaxis in this process is unknown. Recent research with Td has revealed that the structure of the chemotaxis system in spirochetes differs from canonical systems in several regards 29 . Their chemotaxis arrays have unique linear symmetry and contain a novel CheW variant that possesses an additional C-terminal domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The question thus emerges: what are the molecular origins of the p2 symmetric architecture seen in this study? While to the best of our knowledge a p2 symmetric architecture has not yet been reported for the E. coli chemosensory array, a recent publication by Muok et al describes an unusual chemosensory array organisation in the spirochete Treponema denticola [39]. Similar to the p2 lattice described in this study, the atypical T. denticola array exhibits a linear CheA arrangement, including rings involving interactions between a classical CheW and a spirochete-specific CheW variant that are analogous to the (A.P5/W/W)2 rings seen in our model.…”
Section: Implications Of the Observation Of P2-symmetric Chemosensorymentioning
confidence: 94%